Neuausrichtung der Europapolitik - Volker Ratzmann (Wirtschaftsdienst, 2014)
– The economic power of the euro countries should be strengthened by growth incentives, in the form of an additional European growth fund, which should also be funded by financial transaction tax revenues. The current level of debt requires a strengthening of government revenues. Taxes must be collected more effectively, and tax harmonisation should eliminate imbalances in the EU. The banking union should be a central component of crisis management. Moreover, the lingering debt problem must be solved.
Keywords: G18; G28; 330; Wirtschaftswachstum; Wirtschaftliche Anpassung; Haushaltskonsolidierung; Eurozone